Level of Anxiety About Covid-19 in the Community RT I RW XII Kelurahan Manyar Sabrangan Surabaya - Rini Ambarwati; Yuniar Sulistyo Kartika Sukma; Albertha Lembunai Tat; Nur Hasanah (International Journal of Advanced Health Science and Technology, 2023)
Anxiety is a judgement and emotional response to something dangerous. Anxiety is strongly instability, decreased income, sudden layoffs, difficulty finding employment, and loss of life in a matter of days after contracting Covid-19 which could cause anxiety. The purpose of this study was to determine the level of anxiety about Covid-19 in the community of RT I RW XII Manyar Sabrangan Village. The sampling technique in this study used an incidental sampling technique with a total of 110 people. The results of this study indicate that people with anxiety levels based on age mostly experience severe anxiety with the highest presentation at the age of 18-25 years (57.15%), while based on education most experience moderate anxiety with the highest presentation in junior high school education (33.3%) and anxiety levels based on work almost all experience moderate anxiety with the highest presentation as self-employed (88.88%). It is expected for every community to continue to discipline themselves in implementing health protocols such as wearing masks, washing hands, maintaining distance and carrying out Covid-19 vaccinations.